Interaction Hegemony in Soccer Diplomacy: Social Media Communication Strategies of Four AFC Champions League Two Clubs - Ridha Handayani; Rini Sudarmanti (Journal Research of Social Science, Economics, and Management, 2026)
This research analyzes the social media communication strategies of four Southeast Asian football clubs in the AFC Champions League Two Group G competition, namely Persib Bandung (Indonesia), Selangor FC (Malaysia), True Bangkok United (Thailand), and Lion City Sailors (Singapore). The study used a content analysis method on 1,349 uploads during the period of November 27-December 10, 2025. The results of the study found "97% Anomaly", which is a condition when Persib Bandung controls 97.64% of the group's total digital interactions. The findings show that digital interaction is not linearly correlated with the number of followers, but rather is the result of systemic management of four pillars, namely corporate identity alignment, dialogical relational structure, integrated content balance, and cross-platform coordination. Dialogical-participatory communication was shown to produce a 526-fold higher engagement multiplier than the monological-institutional pattern. In addition, video formats were found to be 70% more effective at triggering audience engagement than static images. Strategic positioning analysis shows that the effectiveness of digital communication is determined more by the quality of the strategy than the scale of the audience. Theoretically, this study enriches the literature on sports communication in Southeast Asia. In practical terms, these findings offer a strategic design for professional football clubs to build relational, adaptive and sustainable social media communications.